Analysis of the Association Between Adolescent Lifestyle and the Risk of Early-Onset Hypertension Among Grade X–XI Students at SMA PGRI 2 Banjarmasin - Rizkullah, Muhammad Raihan; Hiryadi; Harun, Lukman (Fakultas Kedokteran, Universitas Papua, 2025)
Adolescents constitute a productive age group with a strategic role in national development. Adolescence represents a complex transitional period from childhood to adulthood, characterized by significant changes in physical, cognitive, emotional, and social domains. Hypertension is one of the most lethal non-communicable diseases worldwide and is often referred to as a silent killer because many affected individuals are unaware of their condition. This study aimed to analyze the association between the lifestyle of Grade X–XI students at SMA PGRI 2 Banjarmasin and the risk of early-onset hypertension. A quantitative approach with a cross-sectional design was employed. The study population consisted of 204 students, with a sample of 68 students selected using proportional stratified random sampling. Data were collected through questionnaires and direct blood pressure measurements. Data analysis was performed using the Spearman rho statistical test to examine the association between variables. The results demonstrated a statistically significant association between adolescent lifestyle and the risk of early-onset hypertension (p < 0.001), with a correlation coefficient of −0.657. This negative correlation indicates that poorer adolescent lifestyle is associated with a higher risk of early-onset hypertension.